Prevalence of anemia and its risk factors among supplemented and non-supplemented pregnant women in Sulaimani city Kurdistan-Iraq - Q. Pirot, Aras; M. Weli, Sardar (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Anemia is a serious global public health problem that particularly affects pregnant women. Objectives: The objectives of the study were to find out the prevalence of anemia and its associated risk factors among supplemented and non-supplemented pregnant women. Cases and methods: Six hundred and forty-one blood samples were collected through simple random sampling from pregnant women and controls. The collected data from the participants included age, education, residence, and obstetrical related factors, and blood samples were taken for blood tests. Results: One hundred and sixty-four (74.2%) and 73 (34.9%) of non-supplemented and supplemented pregnant women respectively were found to be anemic. Age of pregnant women, gestational age, high gravidity, employment status, level of education, body mass index, daily activity, and blood pressure were significantly associated with anemia in the supplemented group. However, in the non-supplemented group only gestational age and high gravidity factors were significantly associated with anemia. There were significant differences between the rate of anemia among supplemented and non-supplemented pregnant women in all factors except birth intervals. The frequencies of low serum ferritin level among non-supplemented and supplemented anemic pregnant women were 137 (83.5%) and 45 (61.6%) respectively. Conclusion: The prevalence of anemia was very high among non-supplemented compared to supplemented pregnant women in Sulaimani city in Kurdistan-Iraq. The risk factors that were associated with anemia were: Age of pregnant women, gestational age, high gravidity, employment status, level of education, body mass index, daily activity, and blood pressure.